(untitled) - Sobel, Milo (New York, 2010)
You can learn the nuts and bolts of an MBA using this step-by-step guide. It's all here-- the essentials of marketing, accounting, finance, and more-- presented in the most clear and comprehensible way possible.
Keywords: Management,Quản trị